2018
DOI: 10.1136/thoraxjnl-2017-211152
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory support or respiratory muscle training as adjuncts to exercise in obese CPAP-treated patients with obstructive sleep apnoea: a randomised controlled trial

Abstract: Results, NCT01155271.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
(28 reference statements)
0
20
0
3
Order By: Relevance
“…In multivariate analysis, determinants of PWV progression are old age and hypertension. Optimal management of OSA-associated comorbidities is needed for patients on CPAP treatment [60,61] in order to slow deterioration in arterial stiffness, reduce the occurrence of late cardiovascular events and to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, determinants of PWV progression are old age and hypertension. Optimal management of OSA-associated comorbidities is needed for patients on CPAP treatment [60,61] in order to slow deterioration in arterial stiffness, reduce the occurrence of late cardiovascular events and to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, weight loss plus CPAP have synergistic effects on weight and metabolic parameters compared with each intervention alone [83]. In obese patients with OSA on CPAP, noninvasive ventilation or respiratory muscle training as adjuncts to exercise have recently been shown to significantly reduce waist circumference and blood pressure [84].The evidence supports a combined treatment strategy in obese OSA.…”
Section: Impact Of Cpap Treatment On Adipose Tissue and Ectopic Fatmentioning
confidence: 99%
“…In a previous study, we have demonstrated that OSA phenotypes are specifically influenced by the above-mentioned environmental factors [9]. Thus, taking into consideration the patient's ecosystem will provide a sound basis for personalized medicine and a multimodal management of OSA, including lifestyle interventions and an exercise programme to complement continuous positive airway pressure (CPAP) treatment [35]. Whereas OSA severity assessed by AHI was similar in both groups, OVS patients exhibited less symptoms related to sleep-disordered breathing and reported less excessive daytime sleepiness compared to the OSA alone population.…”
Section: Plos Onementioning
confidence: 99%